Protective effect of erdosteine against naphthalene-induced oxidative stress in rats [Sıçanlarda naftalen ile oluşturulan oksidatif hasara karşı erdostein'in koruyucu etkileri] - (:unkn) unknown (Marmara University, 2010)
In this study the role of free radicals in naphthalene-induced toxicity and the protection by erdosteine are investigated. Female Sprague-Dawley rats were treated with a single oral dose of 1100 mg naphthalene/kg in corn oil. Erdosteine was given 50 mg/kg/day orally for 3 days before naphthalene treatment and rats were decapitated 24 hours after naphthalene administration. Liver and kidney tissue samples were taken for determination of malondialdehyde (MDA), glutathione (GSH), Na+, K+-ATPase and myeloperoxidase (MPO) activities. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN) and creatinine levels and lactate dehydrogenase (LDH) activity were measured in the serum samples, while TNF-α, IL-1β, IL-6, 8-hydroxy-2'-deoxyguanosine (8- OHdG) and total antioxidant capacity (AOC) were assayed in plasma samples. Naphthalene administration caused a significant decrease in tissue GSH levels, Na+, K+-ATPase activity and plasma AOC levels, which was accompanied with significant increases in tissue MDA levels and MPO activity. Moreover the pro-inflammatory mediators (TNF-α, IL-β, IL-6), 8- OHdG, LDH activity, AST, ALT, creatinine and BUN levels were significantly increased in the naphthalene group. On the other hand erdosteine treatment prevented all these biochemical changes induced by naphthalene. In conclusion, it seems likely that erdostein protects tissues by inhibiting neutrophil infiltration, balancing the oxidant-antioxidant status and regulating the generation of inflammatory mediators.
Keywords: Erdosteine; Glutathione; Lipid peroxidation; Myeloperoxidase; Naphthalene